Kepadatan dan Keanekaragaman Avifauna di Taman Hutan Raya (Tahura) Banten: Analisis dengan Metode Point Count - Haryandi, Yopi; Fatriani, Rizka; Nugraheni, Latif Sofiana; Mukhoyyaroh, Qiswatun; Utami, Noviani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Birds play a crucial ecological role in maintaining forest ecosystem balance. However, environmental changes and anthropogenic pressures can affect bird population density and diversity in a given area. This study aims to identify the population density and diversity of birds in Banten Grand Forest Park. Data collection was conducted on June 22–23, 2024, using the Point Count method at five observation points within the Tahura Banten area. Observations were carried out in the morning (06:00–10:00 WIB) and in the afternoon (15:00–18:00 WIB). Population density was analyzed using the formula D = N/A, while bird diversity was assessed using the Shannon-Wiener Index. The results recorded 95 individual birds, classified into 25 species and 16 families. The Black-capped Babbler (Pellorneum capistratum) and the Common Iora (Aegithina tiphia) were the species with the highest density, reaching 2.55 individuals per hectare. The Shannon-Wiener Index calculation yielded a value of H’ = 3.03, indicating a high level of species diversity in the study area. These findings suggest that Tahura Banten remains an important habitat for various bird species. This study highlights the importance of forest ecosystem conservation in Banten Grand Forest Park to ensure the sustainability of bird populations and biodiversity in the region. Keywords: Population density, bird diversity, Point Count, Tahura Banten, conservation